The Impact of Shariah Compliant and GCG Disclosure on Company Value (Study of Shariah Banks Listed on the IDX) - Dian Firdaus; Hilda Maulida (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This quantitative study rigorously investigated the impact of Shariah Compliance disclosure (RUBR, DPS) and Good Corporate Governance (GCG) mechanisms (Independent BOC, UNDW, IBC) on the Return on Assets (ROA) of four Indonesian Islamic banks (2019-2024). Employing a causal-comparative design and CEM methodology, individual T-tests revealed statistically insignificant effects of the Independent BOC (p = 0.0511) and IBC (p = 0.1173) on ROA. Conversely, UNDW (p = 0.0036) and RUBR (p = 0.0035) demonstrated statistically significant influences. The aggregate impact, assessed by the F-test (p = 0.00058), was substantial, with an R-squared of 0.4627. These findings underscore the salient roles of underwriter reputation and minimizing interest-bearing liabilities in enhancing ROA within Indonesian Islamic banking.